The Privacy of the Insurance Contract for Self-Driving Cars: A Comparative Study - Al-Saeedi, Lubna Abdul Hussein Easa Al-Saeedi (Journal of Legal Sciences, 2023)
Developments in self-driving car technology have already begun to disrupt car manufacturing and insurance considerations. Likewise, new questions have arisen, especially if we know that their damage may be technical, so the technological error may also need to be considered with driver error, so these phenomena began to spark ideas. New information about who bears the risk, how insurance takes place, and the extent to which personal data is compromised when viewed by insurance companies.